1980
DOI: 10.1136/thx.35.5.328
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoalveolar lavage fluid cell counts in cryptogenic fibrosing alveolitis and their relation to therapy.

Abstract: Bronchoalveolar lavage was used to sample inflammatory cells from the lungs of 51 patients with cryptogenic fibrosing alveolitis (CFA) (24 smokers, 12 ex-smokers, and 15 non-smokers). The smokers with CFA have been compared with 15 smoking control subjects in whom there was no radiographic abnormality or clinical evidence of chronic bronchitis. Significantly lower volumes of lavage fluid were recovered from the smokers with CFA (p < 0 001) and the fluid contained lower percentages of macrophages (p < 0Ol), ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
108
3
3

Year Published

1984
1984
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 222 publications
(122 citation statements)
references
References 15 publications
8
108
3
3
Order By: Relevance
“…The mean percentage of neutrophils in our patients with IPF was much lower than the values reported by Reynolds et al (1977, 33%) and Weinberger et al (1978, 21.3%), but is comparable to that reported by Haslam et al (1980). The mean percentage of eosinophils in our study was comparable to that reported by Reynolds et al (1977) and Weinberger et al (1978).…”
Section: Discussioncontrasting
confidence: 47%
See 4 more Smart Citations
“…The mean percentage of neutrophils in our patients with IPF was much lower than the values reported by Reynolds et al (1977, 33%) and Weinberger et al (1978, 21.3%), but is comparable to that reported by Haslam et al (1980). The mean percentage of eosinophils in our study was comparable to that reported by Reynolds et al (1977) and Weinberger et al (1978).…”
Section: Discussioncontrasting
confidence: 47%
“…On the other hand, Reynolds et al (1977) and Weinberger et al (1978) reported that the percentage of lymphocytes in the BALF of patients with IPF was not increased. Other investigators (Haslam et al 1980 ;Ozaki et al 1982) reported that it was only slightly increased in some patients with IPF.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations